AB0051 Angiogenic and Anti-Angiogenic Factors: Biomarkers for Large Vessel Vasculitis?. (15th July 2016) - Addimanda, O.; Pulsatelli, L.; Boiardi, L.; Assirelli, E.; Pazzola, G.; Muratore, F.; Dolzani, P.; Versari, A.; Casali, M.; Magnani, L.; Bottazzi, B.; Mantovani, A.; et al.
Abstract : Background: Large vessel vasculitides (LVV) – Takayasu Arteritis (TA) and Giant Cell Arteritis (GCA) are inflammatory diseases of the aorta and its main branches. A cytokine cluster involving the IL-6 – IL-17 axis as well as another one centring on the IL-12-IFN-γ axis are involved in LVV pathogenesis. (1) Disease activity could be evaluated by measuring ESR and CRP as well as by using imaging techniques (Doppler Ultrasound, Computed Tomography scan, Magnetic Resonance Imaging or Positron Emission Tomography scan – CT/PET) and specific scoring systems (Indian Takayasu's Arteritis Activity Score - ITAS and Kerr/National Institutes of Health index - Kerr / NIH) . To date, angiogenic factors have been evaluated but specific biomarkers for disease activity are still lacking (2) Objectives: The aim of our study was to evaluate angiogenic and anti-angiogenic factor expression in LVV, in order to evaluate their role as biomarkers. Methods: We enrolled 67 patients with LVV [TA (40, 59.7%) or GCA (27, 40.3%)] and 50 Normal Controls (NC). Angiogenic (angiopoietin-1, angiopoietin-2, Fibroblast Growth Factor2 – FGF-2, Vascular Cell Adesion Molecule1 – VCAM-1, Vascular Endothelial Growth Factor – VEGF) and anti-angiogenic (angiostatin, Endostatin-1, Pentraxin 3 – PTX3) factors were analysed using enzyme-linked immuno-sorbent assay (ELISA). Disease activity was evaluated according to Kerr (≥2) and ITAS (≥1) scores, only 47 (70.1%) patients underwent CT/PET. Serum levels of angiogenic and anti-angiogenic factors were compared among active LVV, inactive LVV and NCs. When evaluating disease activity according to CT/PET, it was considered active if SUV >2. Statistical analysis was performed utilizing Mann Whitney, Kruskal Wallis for multiple comparison and Dunn's post hoc test, using Graph Pad Prism software. Results: No significant differences were found between LVV and NCs in angiogenic factors. Conversely, anti-angiogenic factors were all significantly increased in LVV (both GCA and TA) in comparison with NCs (angiostatin: TA vs NC, p<0.0001; GCA vs NC, p=0.0008; endostatin: TA vs NC, p=0.0002; GCA vs NC, p=0.001; PTX-3: TA vs NC, p<0.0002; GCA vs NC, p=0.001). Stratifying patients according to disease activity (with Kerr and Itas scoring systems, as well as taking into account CT/PET), no significant differences were found in angiogenic factors. Anti-angiogenic factors were significantly higher both in active LVV and inactive LVV compared with NCs (p<0.05). Conclusions: Our data show an imbalance between angiogenic and anti-angiogenic factor levels in serum. No disease activity related changes were observed for these factors. References: Weyand CM, Goronzy JJ. Immune mechanisms in medium and large-vessel vasculitis. Nat Rev Rheumatol 2013;9:731–740; Villa I, Bilbao MA, Martìnez-Taboada VM. Advances in the diagnosis of large vessel vasculitis: identification of biomarkers and imaging studies. Rheumatol Clin 2011;7:S22-S27 Disclosure of Interest: None declared